2007
DOI: 10.1016/j.vaccine.2006.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a fimbrial versus an autotransporter display system for viral epitopes on an attenuated Salmonella vaccine vector

Abstract: Attenuated Salmonella have been used as vectors to deliver foreign antigens as live vaccines. We have previously developed an efficient surface-display system by genetically engineering 987P fimbriae to present transmissible gastroenteritis virus (TGEV) C and A epitopes for the induction of anti-TGEV antibodies with a Salmonella vaccine vector. Here, this system was compared with an autotransporter protein surface display system. The TGEV C and A epitopes were fused to the passenger domain of the MisL autotran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Previous addition of the spiC promoter, which is activated in antigen-presenting cells, was used successfully to express the MisL protein or the 987P fimbriae of E. coli as viral epitope carriers on the surface of a Salmonella vaccine vector. Oral immunization experiments in mice also suggested improved in vivo expression by showing better humoral immune responses against the foreign antigens [ 10 , 24 ]. Thus, we prepared a similar promoter tandem construct by inserting the spiC promoter between the nirB promoter and the Shine Delgarno site for MisL transcription (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous addition of the spiC promoter, which is activated in antigen-presenting cells, was used successfully to express the MisL protein or the 987P fimbriae of E. coli as viral epitope carriers on the surface of a Salmonella vaccine vector. Oral immunization experiments in mice also suggested improved in vivo expression by showing better humoral immune responses against the foreign antigens [ 10 , 24 ]. Thus, we prepared a similar promoter tandem construct by inserting the spiC promoter between the nirB promoter and the Shine Delgarno site for MisL transcription (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study suggested that location on the bacterial surface was even more important for immunity than high abundance or immunodominance since Salmonella mainly survive in antigen-presenting cells, rendering surface antigens more accessible to the cell for processing and presentation [ 30 ]. Second, surface-exposed foreign epitopes presented as multimers induced better antibody responses than the same epitopes presented as monomers on a Salmonella vaccine vector [ 10 ]. Because it is capable of expressing antigens on a Salmonella surface, the MisL protein has the advantage of tolerating large fragments of proteins in a fusion construct.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface-exposed foreign epitopes are often presented as multimers and could induce better immune responses than the same epitopes presented as monomers in a Salmonella vaccine (31). Therefore, antigen expressed on Salmonella surface using surface display system can induce better CD4 þ T response.…”
Section: Discussionmentioning
confidence: 99%
“…Although autodisplay has become a system of choice for recombinant protein expression for various applications, there are limited studies comparing the effects of secreted versus cell surface-bound antigen on host immune responses ( 33 ). Nevertheless, some studies have suggested that protrusion of the target antigen away from bacterial cell surface structures may facilitate protective immunity ( 34 ). This implies that the mode of antigen presentation to the immune system, rather than intrinsic properties of the antigen and/or expression levels, can determine immunogenicity.…”
Section: Introductionmentioning
confidence: 99%